Effect of Auxin 2,4-D and NAA on Induction Callus and Adventitious Shoots and Roots regeneration from half Shoot Tips Culture of white ginger (Zingiber officinale var. Roscoe) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2020)
This study was conducted in plant tissue culture laboratory of Agriculture College, Basrah university, Iraq during the period 2018-2019. The aims of this study were to find out the effect of different concentration of two auxin 2,4-D and NAA to induce the callus and regeneration of adventitious shoots and roots of Zingiber officinale Rosc. white via culture of half shoots tips. Results of the present study revealed that medium of MS containing 1.0 mg.l-1  2,4-D + 0.5 mg.l-1 BA + 500 mg.l-1 PVP caused primary callus formation (100%) with high diameter, fresh and dry weight of callus (2.26 cm, 1.95 mg and 0.12 mg); respectively. Results also showed that MS medium containing 30.0 mg.l-1 + 3 mg.l-1 2ip + 500 mg.l-1 PVP caused the higher primary callus formation (100%) within (11.33 days) and a higher diameter, fresh and dry weight of callus (2.50 cm , 0.86 mg and 0.14 mg); respectively. However adventitious roots were regenerated from primary callus in all concentration of NAA, whereas the medium MS containing 10.0 mg.l-1 NAA was gave the highest number and length of roots (13.33 root .callus and 2.83cm). When the activated charcoal (500 mg.l-1) was replaced by PVP in the same medium containing 30.0 mg.l-1 NAA response was found at the end of the incubation period, small green adventitious shoots and white roots were regenerated.